Ser Quilombola e ser de Pinhões: dinâmicas e experiências de uma produção do lugar - Lúnia Costa Dias (2014)
This dissertation aims to articulate some elements, practices and dynamics that constitute the production of a 'locality' in the community of Pinhões, situated in Santa Luzia city, in the northern of metropolitan region of Belo Horizonte. The issue of the research came up from over five years of monitoring local discussions about the affirmation of quilombola identity in Pinhões. This research sought to analyse and reflect about the concerns of some residents of Pinhões in registering these dynamics, especially women members of Womens Cultural Association of Pinhões. Therefore, the analysis will focus on the dynamic and cultural experiences highlighted by the subjects involved in the course of this research. The reflections go through Womens Cultural Association of Pinhões and their definitions about Pinhões Quilombola by observing the dynamics and daily experiences, as well the dimensions that weave the history of the place. This exercise reveals a condition of distances and similarities between two plans/dimensions of analysis that goes through the polarities of be residents of Pinhões and be quilombolas. Those dimensions establish a critical condition of a "being" and "not being a quilombola, a condition at the same time established and constitutive. It is about the experiences, practices and dynamics of autonomy from the 'being' that creates a territorialized existence and constitutes a 'locality' with their own dynamics and their own cultural elements in which Pinhões moves over the possibilities of affirmation of quilombola identity.